Incidence of metallo-beta-lactamase-producing Pseudomonas aeruginosa in diabetes and cancer patients - Varaiya Ami; Kulkarni Manasi; Bhalekar Pallavi; Dogra Jyotsana (Wolters Kluwer Medknow Publications, 2008)
Metallo-beta-lactamase (MBL)-producing Pseudomonas aeruginosa strains have been reported to be an important cause of nosocomial infections. There is not enough information from India regarding their prevalence in diabetic and cancer patients. The present study was undertaken over a period of one year from January to December 2006 to study the incidence of MBL P. aeruginosa and the clinical outcome in diabetes and cancer patients admitted to S.L. Raheja Hospital, Mumbai. Two hundred and thirty isolates of P. aeruginosa were obtained from different samples of patients. These isolates were subjected to susceptibility testing to anti-pseudomonal drugs as per CLSI guidelines. They were further screened for the production of MBL by disc potentiation testing using EDTA-impregnated imipenem and meropenem discs. Of the 230 isolates of P. aeruginosa, 60 (26%) isolates were found resistant to carbapenems (both imipenem and meropenem) and 33 (14.3%) were found to be MBL producers. Of the 33 MBL-producing isolates, 24 (72.7%) were diabetic patients, six (18.1%) were cancer patients and three (9%) patients had both diabetes and cancer. Five (15.1%) patients responded to the combination therapy of colistin, piperacillin with tazobactam and amikacin, while 28 (84.8%) patients responded to the combination therapy of amikacin, piperacillin with tazobactam and gatifloxacin. Thus, the rapid dissemination of MBL producers is worrisome and necessitates the implementation of not just surveillance studies but also proper and judicious selection of antibiotics, especially carbapenems.